O REGIME MILITAR NA (DES)MEMÓRIA DA EDITORA ABRIL: A REVISTA ESCOLA E A DIFUSÃO DA LEI 5.692/71 - Daniel Revah; Maria Rita de Almeida Toledo (Associação Sul-Rio-Grandense de Pesquisadores em História da Educação (ASPHE), 2011)
This article shows the first results of a research that is in progress about the magazine ESCOLA from publisher Abril. It´s a short-lived magazine: 27 copies from october, 1971 to april, 1974. The first edition was number 0, and number 1 was published some months later, in March, 1972, and then, it was published monthly up to its last copy (n. 26). At this time, many editions showed prospectus that would be used for the construction of two books: the Book of reformation (october, 1971 to june, 1972) and Helpful resources for teaching (between november, 1973 and april, 1974). In the first copy the magazine is shown as dialogue and co-operative instrument with elementary teacher as the first pedagogical magazine that was created with the resources of journalism, with journalistic form at the service of pedagogical contents. In this production, this publication is known as a specific kind of press that has two strategies of cultural interference: editorial interference that assumes pedagogical knowledge by means of the journalistic pattern, to increase the market of publisher Abril products; as interference in the educational field, by publishing, organizing, and prescribing the necessary actions for the accomplishment of reformation. In this perspective, one can analyze the main resources the magazine used, emphasizing the ones that remain during its existence and planned the editorial form that was used. ESCOLA is also related to the history that publisher Abril has constructed on its trajectory in this period.